Pirin is a prognostic marker of human melanoma that dampens the proliferation of malignant cells by downregulating JARID1B/KDM5B expression - Penas, Cristina; Arroyo-Berdugo, Yoana; Apraiz, Aintzane; Rasero, Javier; Muñoa-Hoyos, Iraia; Andollo, Noelia; Cancho-Galán, Goikoane; Izu, Rosa; Gardeazabal, Jesús; Ezkurra, Pilar A.; Subiran, Nerea; Alvarez-Dominguez, Carmen; et al. (Scientific Reports, 2023)
Originally considered to act as a transcriptional co-factor, Pirin has recently been reported to play a role in tumorigenesis and the malignant progression of many tumors. Here, we have analyzed the diagnostic and prognostic value of Pirin expression in the early stages of melanoma, and its role in the biology of melanocytic cells. Pirin expression was analyzed in a total of 314 melanoma biopsies, correlating this feature with the patient’s clinical course. Moreover, PIR downregulated primary melanocytes were analyzed by RNA sequencing, and the data obtained were validated in human melanoma cell lines overexpressing PIR by functional assays. The immunohistochemistry multivariate analysis revealed that early melanomas with stronger Pirin expression were more than twice as likely to develop metastases during the follow-up. Transcriptome analysis of PIR downregulated melanocytes showed a dampening of genes involved in the G1/S transition, cell proliferation, and cell migration. In addition, an in silico approach predicted that JARID1B as a potential transcriptional regulator that lies between PIR and its downstream modulated genes, which was corroborated by co-transfection experiments and functional analysis. Together, the data obtained indicated that Pirin could be a useful marker for the metastatic progression of melanoma and that it participates in the proliferation of melanoma cells by regulating the slow-cycling JARID1B gene.
CRIS-Team Scopus Importer:2023-06-30